N-Donor flexible ligands for constructing polyoxometalate-based metal–organic frameworks as multifunctional electrocatalysts. Issue 14 (23rd March 2022) - Zhou, Qian; Yao, Jin-Zhen; Sun, Jing; Li, Xiao; Bao, Si-qi; Su, Zhong-min
Abstract : Two POMOFs, CUST-631 and CUST-632, were synthesized by a hydrothermal method and then were directly prepared as electrode materials to explore the electrocatalytic properties for reduction of BrO3 − and NO2 − ions and oxidation properties towards AA. Abstract : Polyoxometalates (POMs) can participate into metal–organic frameworks to construct POM-based metal–organic frameworks (POMOFs) with excellent redox properties, displaying potential photo- and electrochemical applications. Here, two POMOFs [M2 (btbu)4 (H2 O)2 (SiW12 O40 )] [M = Ni for CUST-631 and Co for CUST-632 ; btbu = 1, 4-bis(1, 2, 4-triazole-1-yl)butane] were synthesized by a hydrothermal method and characterized by PXRD, IR and TG. CUST-631 and CUST-632 are directly prepared as electrode materials (denoted as 631-CPE and 632-CPE) to explore their electrocatalytic properties. The experimental results show that 631-CPE and 632-CPE exhibit good electrocatalytic reduction of BrO3 − and NO2 − ions and great oxidation properties towards AA.